Between the Listener and the Talker: Connectivity Options - Thibodeau, Linda M. (Seminars in Hearing, 2020)
Hearing aids are often not sufficient for optimal communication between a listener and a talker. Therefore, numerous options for wireless connectivity between the listener and the talker designed to improve communication have become widely available. From the original wireless option of the induction loop system, most of the current solutions involve a digital signal with high quality and limited interference. Many are proprietary and only operate with a given manufacturer's devices, while others are more universal as long as the digital receiver can be connected to the listener's personal device. In addition, connectivity options to assist those with hearing loss are now readily available on the smartphone which can be used as a remote microphone. Therefore, it is paramount that the available wireless protocols be considered relative to the listener's experience with wireless technology so that solutions may be offered that are efficient, economical, and effective.
Keywords: remote microphone; hearing aid; wireless; Bluetooth